RESPONSE TO GROWTH AND YIELD OF PAK CHOY WITH DIFFERENT DOSES OF ARBUSCULAR MYCORRHIZAL FUNGI - Netti Herawati; Armansyah Armansyah; Miftahul Jannah (JERAMI)
Pakcoy is a potential horticultural commodity to be cultivated because it is in demand by many Indonesians, especially for Chinese cuisine lovers. The demand for pakcoy always increases every year. However, it has not been supported by sufficient pakcoy productivity. The reasons include the decreasing area of productive land (harvest area). One of the efforts to overcome the reduced harvest area is to expand agricultural land by utilizing marginal land such as Ultisol. Cultivation activities on Ultisol certainly require more optimal handling, including the addition of lime and inorganic fertilizers in large quantities. However, this can damage the potential of the land if done for a long time. Therefore, other alternatives are needed in handling cultivation on Ultisol, one of which is the addition of biological agents such as AMF. For this reason, research has been conducted on the Response to Growth and Yield of Pakcoy Plants (Brassica rapa subsp. chinensis) by Giving Doses of Arbuscular Mycorrhizal Fungi. The research aims to get the best dose for the growth and yield of pakcoy plants. This study used a completely randomized design with four treatments and four replications, namely AMF doses of 0 g/plant, 5 g/plant, 10 g/plant, and 15 g/plant. Observation data were analyzed by the F test at a 5% level if the Fcount is greater than Ftable, followed by the DNMRT test at a 5% level. The results showed that the application of AMF could improve the growth and yield of pakcoy plants. The best dose of AMF was 10 g/plant